Synucleins - Biochemistry and Role in Diseases 2020
DOI: 10.5772/intechopen.83648
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phenylalanine and Its Metabolites in Health and Neurological Disorders

Abstract: Phenylalanine, an amino acid, is a "building block" of protein. Phenylalanine is a component of food sources and also derived through supplementation. In current treatment, phenylalanine is prescribed as anti-depressant agent. The present study reviewed the possible antidepressant potential of phenylalanine. We reviewed data using the major databases, namely, Web of Science, SciFinder, Google Scholar, and PubMed. This manuscript provides a brief overview of the role of phenylalanine in depressive disorders. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Phenylalanine is a component of food sources and also derived through supplementation. In current treatment, phenylalanine is prescribed as anti-depressant agent (Akram et al 2020). This acid is also used in the treatment of depression, migraine, painful menstruation, and Parkinson's disease (Onuegbu et al).…”
Section: Resultsmentioning
confidence: 99%
“…Phenylalanine is a component of food sources and also derived through supplementation. In current treatment, phenylalanine is prescribed as anti-depressant agent (Akram et al 2020). This acid is also used in the treatment of depression, migraine, painful menstruation, and Parkinson's disease (Onuegbu et al).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the health benefits of the essential amino acids produced during fermentation have been extensively investigated. For example, phenylalanine, a precursor to tyrosine, is used for the biosynthesis of catecholamines that are known to be effective in depression, pain, and skin disorders [ 25 ]. Jansen et al [ 26 ] also demonstrated that lysine was required for healthy tissue function, growth, calcium uptake, and healing as well as the immune system.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins also have an important role in the formation of biomolecules, such as enzymes (Alberts et al, 2002). Protein is closely related to the immune system, low protein intake causes on a decrease of immune system (Akram et al, 2020). The water level in Kian marine worms was lower than in wawo worms (Palola sp.)…”
Section: Discussionmentioning
confidence: 97%
“…Phenylalanine has a function as an antidepressant. Phenylalanine plays a role in the formation of neurotransmitters such as dopamine, nor-epinephrine, and epinephrine (Akram et al, 2020). The amino acid threonine acts as an immunostimulant by increasing the thymus gland (Abbasi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%